Periodic structures with spherical alumina particles: Transmission and reflection spectra - Miskevich, A.A.; Loiko, V.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2013)
Coherent transmission and reflection coefficients of individual monolayers of
spherical alumina particles in the wavelength range from 0.3 to 1.0 μm and multilayers
consisting of a set of such monolayers are computed. Quasi-crystalline approximation of
the theory for multiple scattering of waves and the transfer matrix method are used.
Three types of coherent transmittance minima inherent to close-packed regular disperse
systems are singled out and described. Spectra of a glass plate with one-sided and
double-sided coating with alumina particles are analyzed. Systems for creating
antireflection coatings, diffuse light scattering structures, selective and nonselective
filters of transmitted and reflected light are considered.